2013
DOI: 10.1007/s10113-013-0576-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate trends and impacts on crop production in the Koshi River basin of Nepal

Abstract: Understanding crop responses to climate is essential to cope with anticipated changes in temperature and precipitation. We investigated the climate-crop yield relationship and the impact of historical climate on yields of rice, maize and wheat in the Koshi basin of Nepal. The results show significant impact of growing season temperature and precipitation on crop production in the region. Rice, maize and wheat cultivated at altitudes below 1,100, 1,350 and 1,700 m amsl (above mean sea level), respectively, suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 36 publications
3
59
0
Order By: Relevance
“…These basins provide water not only for agriculture, but also for forestry and fisheries as well as urban and industrial purposes (Sikka and Ringler 2009). Recent studies (Yu et al 2013;Rasul & Hussain 2015;Bhatt et al 2014;Zhen-Feng et al 2013) have revealed that increased incidences of erratic precipitation, floods, dry spells and landslides, attributed to climate change, have led to decline in agricultural productivity and deterioration of food security. This study investigates whether these scientific findings were mirrored in local people's perception of climate change and its impacts on agriculture and household food security.…”
Section: Methodology Research Design and Study Areamentioning
confidence: 99%
“…These basins provide water not only for agriculture, but also for forestry and fisheries as well as urban and industrial purposes (Sikka and Ringler 2009). Recent studies (Yu et al 2013;Rasul & Hussain 2015;Bhatt et al 2014;Zhen-Feng et al 2013) have revealed that increased incidences of erratic precipitation, floods, dry spells and landslides, attributed to climate change, have led to decline in agricultural productivity and deterioration of food security. This study investigates whether these scientific findings were mirrored in local people's perception of climate change and its impacts on agriculture and household food security.…”
Section: Methodology Research Design and Study Areamentioning
confidence: 99%
“…Agriculture is heavily impacted worldwide by climate change, and yield reduction may result in the decline of food security, especially in mountainous areas [1][2][3][4]. Agriculture requires much water for irrigation, and worldwide roughly 70% of the water is used by agriculture [5][6][7], and increasingly so under population growth pressure [8].…”
Section: Introductionmentioning
confidence: 99%
“…or so, while double cropping is generally limited to areas below 1000 m as.l. [4]. Maize can be successfully cultivated at altitudes up to 2800 m a.s.l.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations